Cellular transport and membrane dynamics of the glycine receptor - Dumoulin, Andrea; Triller, Antoine; Kneussel, Matthias (Frontiers in Molecular Neuroscience, 2010)
Regulation of synaptic transmission is essential to tune individual-to-network neuronal activity. One way to modulate synaptic strength is to regulate neurotransmitter receptor numbers at postsynaptic sites. This can be achieved either through plasma membrane insertion of receptors derived from intracellular vesicle pools, a process depending on active cytoskeleton transport, or through surface membrane removal via endocytosis. In parallel, lateral diffusion events along the plasma membrane allow the exchange of receptor molecules between synaptic and extrasynaptic compartments, contributing to synaptic strength regulation. In recent years, results obtained from several groups studying glycine receptor (GlyR) trafficking and dynamics shed light on the regulation of synaptic GlyR density. Here, we review i) proteins and mechanisms involved in GlyR cytoskeletal transport, ii) the diffusion dynamics of GlyR and of its scaffolding protein gephyrin that control receptor numbers, and its relationship with synaptic plasticity, and iii) adaptative changes in GlyR diffusion in response to global activity modifications, as a homeostatic mechanism.